2015
DOI: 10.1002/jsfa.7056
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek (Trigonella foenum graecum) seed protein isolate: extraction optimization, amino acid composition, thermo and functional properties

Abstract: Fenugreek seed protein extraction was optimized by control of pH and NaCl concentration. FPI could be used as a protein source with remarkable functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 47 publications
8
45
0
1
Order By: Relevance
“…On addition, the reduction of protein particle size by the ultrasonic treatment may be easier to partially dissolve in water during WHC determination, resulting in lower WHC; on the contrary, the small protein particles were more likely to bind with oil because of their larger specific surface area, leading to higher DHC. These results were similar to Fenugreek seed protein (Feyzi et al, 2015).…”
Section: Water and Oil Holding Capacitysupporting
confidence: 86%
See 1 more Smart Citation
“…On addition, the reduction of protein particle size by the ultrasonic treatment may be easier to partially dissolve in water during WHC determination, resulting in lower WHC; on the contrary, the small protein particles were more likely to bind with oil because of their larger specific surface area, leading to higher DHC. These results were similar to Fenugreek seed protein (Feyzi et al, 2015).…”
Section: Water and Oil Holding Capacitysupporting
confidence: 86%
“…When the pH value was far from the isoelectric point, the protein had more negative and positive charges, which led to the increase of electrostatic repulsion and hydration that promoted the protein dissolution and the higher solubility. The similar reports were found in Kiwi fruit seed protein (Deng et al, 2014), Fenugreek seed protein (Feyzi et al, 2015), duck liver protein (Zou et al, 2017) and rice bran protein (Phongthai et al, 2016). Moreover, the solubility of WSP was higher than that of SPO.…”
Section: Protein Solubilitysupporting
confidence: 82%
“…Fenugreek ( Trigonella foenum graecum ) is an important crop belonging to Fabaceae family, which is extensively cultivated in Mediterranean countries and Asia . Studies have shown fenugreek seeds are a great source of plant proteins with total protein content of about 250 to 386 g kg −1 . Among different ingredients, plant protein isolates are highly demanded as food ingredients due to their nutritional and functional properties .…”
Section: Introductionmentioning
confidence: 99%
“…Physical characteristics of biscuit (Width, Thickness and Spread ratio) were affected significantly (p ≥ 0.05) with the increase in the level of FSF as shown in Table 5. Substitution of WF with 5 and 10% of FSF caused decreasing in width of biscuits before baking and increasing in the width after baking .The reason for the decreasing in width may due to the biscuit cell structure being unable to retain gas during proofing (Feyzi et al, 2015;Hefny 2017). Results indicated that, the average width of control biscuit before baking was 23.36 cm, whereas after baking was 24.66 cm.…”
Section: Physical Characteristics Of Wheat Biscuits Supplemented By Rmentioning
confidence: 99%
“…It becomes a good source of protein and its supplementation in wheat flour would help to improve the nutritional quality of the products (Hooda and Jood, 2005;Nassar et al, 2008). It was found that mixing two or more different materials will help to solve the deficiency problem of cereals as low nutritional value by using legumes as food protein source (Rennan et al, 2008;Masood and Batool, 2010;Feyzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%